P689Examination of radiation-induced heart damage using in vitro and in vivo animal models. (15th July 2014) - Kiscsatari, L; Varga, Z; Gorbe, A; Morvay, N; Kovari, B; Lepran, I; Ferdinandy, P; Kahan, Z
Abstract: Purpose: Due to the clinical significance of radiogenic heart damage, it is important to investigate it with clinical and biological methods. Our aim was to develop reliable in vitro and in vivo animal models which help to study the effect of radiation to the heart and to test potential radiation protective materials. Materials and Methods: In in vitro experiments, cardiomyocyte cells were isolated and cultured from newborn rats. The 24-hour cultures were exposed to different doses (5, 10, 15, 20 Gy) of radiation, and the effect was examined at different latency times (0, 24, 48, 72, 96, 120 h). The cells were cultured in a medium containing 1% fetal bovine serum (FBS), but the experiments were completed in serum-free conditions, too. The toxicity of the radiation was evaluated with calcein fluorescence viability assay. In our in vivo model using adult male rats, we developed a selective heart irradiation technique and determined the dose effect curve. The irradiation was carried out with 20, 25, 30 and 40 Gy. After the irradiation animals were continuously monitored for 3 months (weight, heart ultrasound, measurement of circulating cytokines), and at the end of the third month, they were sacrificed and pathological analyses was performed on the cardiac and lung tissues. Results: In the in vitro experiments, 48 hours after 10 Gy irradiation, 50% of the myocytes, grown in medium containing serum were lost, thus, these circumstances seemed to be the most suitable for the study of the radiation damage. We examined the survival of the cardiac muscle cells in serum-free environment, in this case the radiation dose and latency required for a 50%-cell loss were 10 Gy and 24 hours, respectively. In the in vivo model, echocardiography indicated septal wall motion disturbance in animals receiving a radiation dose of 40 Gy 3 months after the treatment. With histological examination, significant myocardial or vascular damage was not found, however, in animals irradiated with the highest dose (40 Gy) mild radiation pericarditis, fibrotic heart lesions and lung damage were observed by hematoxylin-eosin and Crossman's trichrome staining. Conclusions: In accordance with our initial results, the described in vitro and in vivo models appear to be suitable for studying the mechanisms of radiogenic heart damage. In the following experiments, we intend to raise the radiation dose and to extend the time of observation in order to better evaluate the mechanisms of action of radiation and the effects of radiation protective materials.